1999
DOI: 10.1083/jcb.146.4.855
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Expression of β-Catenin Regulates Contact Inhibition, Anchorage-Independent Growth, Anoikis, and Radiation-Induced Cell Cycle Arrest

Abstract: β-Catenin is an important regulator of cell–cell adhesion and embryonic development that associates with and regulates the function of the LEF/TCF family of transcription factors. Mutations of β-catenin and the tumor suppressor gene, adenomatous polyposis coli, occur in human cancers, but it is not known if, and by what mechanism, increased β-catenin causes cellular transformation. This study demonstrates that modest overexpression of β-catenin in a normal epithelial cell results in cellular transformation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
182
3
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(206 citation statements)
references
References 60 publications
20
182
3
1
Order By: Relevance
“…Overexpression of β-catenin, due to genetic alterations of the β-catenin and APC (adenomatous polyposis coli) genes in cancer cells is known to play an important role in tumorigenesis [6]. However, it has also been reported that ectopically overexpressed β-catenin stimulates cell growth in the presence, but not in the absence, of serum [32,33]. Therefore, the physiological level of β-catenin increased by Wnt-3a may co-operate with other factors in the serum to stimulate cell growth.…”
Section: Activities Of Wnt-5amentioning
confidence: 99%
“…Overexpression of β-catenin, due to genetic alterations of the β-catenin and APC (adenomatous polyposis coli) genes in cancer cells is known to play an important role in tumorigenesis [6]. However, it has also been reported that ectopically overexpressed β-catenin stimulates cell growth in the presence, but not in the absence, of serum [32,33]. Therefore, the physiological level of β-catenin increased by Wnt-3a may co-operate with other factors in the serum to stimulate cell growth.…”
Section: Activities Of Wnt-5amentioning
confidence: 99%
“…However, it has become apparent that the cell cycle and WNT signaling are intrinsically linked (16). In a seminal study, WNT-␤-catenin signaling (and ␤-catenin protein levels) were noted to oscillate during the cell cycle, peaking at the G 2 /M transition (17). Since that initial observation, many of the components of the WNT pathway have been shown to play an integral role during cell division.…”
mentioning
confidence: 99%
“…This property of cancer cells has served as a 'golden standard' for cell transformation for three decades (Freedman and Shin, 1974). Second, expression of oncogenes, such as ras (Rak et al, 1995), b-catenin (Orford et al, 1999), epidermal growth factor receptor and ErbB2 (Reginato et al, 2003) in nonmalignant epithelial cells is known to render these cells anoikis-resistant. Third, loss of oncogenes, such as ras, by carcinoma cells was shown to block their in vivo tumorigenicity and anoikis resistance (Rosen et al, 2000;Liu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%